(untitled) (Ustozlar uchun, 2026)
This study explores the complex nature of translating historical texts from English by analyzing their linguistic, cultural, and functional dimensions. Historical texts are characterized by diachronic language features, including archaic vocabulary, obsolete grammatical structures, and culturally bound expressions, which significantly differentiate them from contemporary discourse.The research focuses on key theoretical concepts such as equivalence, adequacy, and translation transformations, with particular emphasis on archaisms, historical realia, and semantic shifts. It also investigates the role of stylistic reconstruction and discourse analysis in preserving the communicative and aesthetic value of the source text.Furthermore, the study highlights the importance of integrating modern approaches, including corpus linguistics and digital tools, in improving translation accuracy. The findings demonstrate that historical text translation requires a multidisciplinary approach combining linguistic competence, cultural awareness, and analytical skills.